The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1530/jrf.0.0860185
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of  -glutamyl transpeptidase in the mouse epididymis and its response to acivicin

Abstract: Summary. \g=g\-Glutamyltranspeptidase (\g=g\-GT), its substrate (GSH) and hydrolytic product (l-glutamic acid) were measured biochemically in mouse reproductive tissues. The epididymal caput and seminal vesicles showed the highest specific activities of \g=g\-GT, while GSH and l-glutamic acid were widely distributed in all tissues. Histochemically, \g=g\-GTdisplayed a strong apical and supranuclear reaction and a moderate basal activity in the ductuli efferentes, a weak luminal reaction in the first, a moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The distribution of 8-glutamyl transpeptidase in the mouse epididymis was examined recently (Agrawal et al, 1989). It was found that the activity of this enzyme was exhibited strongly in the epithelium of the ductuli efferentes and was localized both in supranuclear and basal locations.…”
Section: Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of 8-glutamyl transpeptidase in the mouse epididymis was examined recently (Agrawal et al, 1989). It was found that the activity of this enzyme was exhibited strongly in the epithelium of the ductuli efferentes and was localized both in supranuclear and basal locations.…”
Section: Histologymentioning
confidence: 99%
“…Histochemical localizations of various glycoconjugates (Agrawal et al, 1989) and enzymes (Burkett et al, 1987a,b;Byers and Graham, 1990;Cohen et al, 1976; have inferred secretions of glycoconjugates and amino acids from the epithelium destined for sperm coating and ions in connection with absorption and acid-base balance. Also, structural studies in various animals also have shown granules and apical blebs and protrusions in the nonciliated cells which have the appearance of being extruded or secreted into the lumen (Bakst, 1980;Goyal and Hrudka, 1981;Gray et al, 1983;Hess and Bassily, 1988;Wystub et al, 1989).…”
Section: Secretionmentioning
confidence: 99%
“…As mentioned before, GGT is present in the epididymis, mainly in the head region [13], being the high catalytic activity of GGT in proximal epididymal region, and decreases in the distal region [14,15]. In the present study, it was found that GGT activity is high in the cephalic region, on dates in which sperm are present in the epididymis, something equivalent to what was reported in rat, where they found that GGT concentration was low in immature rats and increased in sexual maturity of rats.…”
Section: Discussionmentioning
confidence: 65%
“…The catalytic activity of GGT is highest in the proximal epididymal regions and decreases toward the distal regions [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…A recent development relevant to how different parts of the epididymis play specific biological roles has been the realization that the anatomical, intraregional segments of the epididymis are likely to be functional units within the organ [4,5]. Experiments using tracer molecules have shown that diffusion in the interstitium between segments is severely restricted by the CTS [4], and it has been shown that the regionalization of biologically relevant properties of the epididymal duct, such as protein and gene expression, often coincide exactly with the limits imposed by the CTS [4,[6][7][8][9][10]. These observations have led to the hypothesis that segmentation of the epididymal interstitium by the CTS provides a physiological basis for epithelial segmental function by creating tightly controlled interstitial microenvironments within different epididymal segments.…”
Section: Introductionmentioning
confidence: 99%